Using YouTube to Increase Learning Motivation as a Resource for Learning Geography in the Digital Age - Fenika, Mila; Zakiatussoleha, Zakiatussoleha; Khotimah, Oot; Zid, Muhammad (Jurnal Multidisiplin Indonesia, 2024)
This research aims to determine the learning motivation of students who use YouTube as a learning resource. This research uses qualitative methods in the Geography learning material "Atmospheric Dynamics" in class X-1 MA-Al-Khairiyah Jakarta. Data sources include sources and documents as supporting data. Based on research results, the majority of respondents (75%) often use YouTube to study geography, and almost all respondents (99%) stated that geography subjects' videos on YouTube helped them understand the material. Various variations of learning videos attract students' attention, and repetition of material that can be done at any time can increase motivation. Learning motivation has a role in fostering enthusiasm, creating feelings of joy and enthusiasm for learning so as to increase knowledge of the natural environment and increase student achievement and interest in learning Geography